Evaluation of Climate Change Indicators for Bagdad City Using Remote Sensing Technology - Moussa, Yusra K. H.; Alwehab, Abdelwehab A. (Iraqi Journal of Science, 2023)
Climate change is a severe problem due to the continuous dynamic changes in urbanization in cities, and reaching it requires high-resolution spatial data represented by using remote sensing technology, as the data of the Space Science Network of NASA was relied on to measure the change in the climate of Baghdad city for a period of four decades 1981-2021, using the climate change equation referred to in the research and then tabulating the data in Excel. The results showed evident changes in the climatic rates, especially during the fourth time cycle; the high rates of temperature and low rates of relative humidity and precipitation indicate that the city’s climate is heading towards drought, and similarities appeared between the rates of atmospheric pressure and wind speed at the height of 10 m in terms of stability and slope.